Effects of Daily Exposure to Saccharin and Sucrose on Testicular Biologic Functions in Mice. Issue 6 (1st December 2016) - Gong, Ting; Wei, Quan-Wei; Mao, Da-Gan; Nagaoka, Kentaro; Watanabe, Gen; Taya, Kazuyoshi; Shi, Fang-Xiong
Abstract: Saccharin sodium consumption is considered safe and beneficial, owing to its very intense sweetness without any associated calories, but supporting scientific data remain sparse and controversial. Herein, we demonstrate that dose-response relationships existed with regard to administration of saccharin or sucrose to mice for 35 days, and this association involved testis-expressed sweet-tasting molecules (taste receptor type 1 subunit 3 [T1R3]; G protein alpha-gustducin [Galpha]). Mouse body weights and testis weights in middle- and low-dose saccharin-treated groups were increased with up-expressions of molecules involved in testicular sweet taste and steroidogenic (middle saccharin: steroidogenic acute regulatory protein [StAR]; P450 cholesterol side-chain cleavage enzyme [CYP11A1]; 17-alpha-hydroxylase/C17, 20-lyase [CYP17A1]; low saccharin: StAR). Moreover, a high-dose saccharin-related decline in reproductive hormone levels and injuries to testis and sperm were observed to be associated with suppression of testicular T1R3 and Galpha, as well as steroidogenic-related factors (StAR; 3-beta-hydroxysteroid dehydrogenase [3-beta-HSD]; CYP11A1; CYP17A1; 17-beta-hydroxysteroid dehydrogenase [17-beta-HSD]), and activation of cleaved caspase-3. However, abnormalities of the testis and sperm in high- and middle-dose sucrose-exposed mice were related to the increased-cleaved caspase-3, but independent of T1R3 and/or Galpha. Collectively, our results clearly suggest that saccharin-induced physiologic effects on testis are associated with testicular T1R3 and Galpha, which differed from sucrose. We hence call for a reassessment of the excessive use of sweeteners in daily life, especially artificial ones, considering their potential side effects.